Asap hio di ranah Minang : komunitas Tionghoa di Sumatera Barat - Erniwati, 1971-; Purwono, Bambang (Yogyakarta : Ombak, 2007)
History of Chinese community in Sumatera Barat Province and close ties between the Chinese and the Minangkabau people in the various fields in the middle of the 19th century to the beginning of 20th century.
Revision of the author's thesis (S2)--Universitas Gadjah Mada, Yogyakarta, 2002.
Mengandungi indeks dan daftar pustaka : p. [153]-166.
Keywords: Chinese -- Indonesia -- Sumatera Barat -- History -- 19th century; Minangkabau (Indonesian people).; Sumatera Barat (Indonesia) -- Ethnic relations -- History -- 19th century